三叉神経障害を生じる病態の鑑別診断について - 高橋, 哲; 千葉, 雅俊 (日本口腔外科学会雑誌, 2020)
Trigeminal neuropathy is characterized by numbness in the skin or mucosa in the distribution of the trigeminal nerves, sometimes in association with pain. Sensory deficits in the lower lip and tongue frequently causes difficulties with speech and eating. Thus, numbness in the trigeminal distribution is more distressin than numbness involving spinal dermatomes.　The differential diagnosis of the causative diseases underlying the trigeminal neuropathy is difficult, because a spectrum of pathophysiological conditions may affect the trigeminal nerves, including traumatic, vascular, inflammatory, demyelinating, infectious, and neoplastic disorders. Moreover, trigeminal neuropathy develops in isolation or in combination with other neurological deficits of nearby cranial nerves or extremity. Trigeminal neuropathy may also be the presenting manifestation of malignancy, autoimmune disease, or vascular hemorrhage or ischemia of the brainstem. Thus, the findings of orofacial numbness necessitate a comprehensive assessment of all aspects of the trigeminal pathways, which may include neurophysiological, radiographic, and laboratory evaluation in addition to the careful medical interview. In this review, we illustrated some of the principal pathological conditions causing trigeminal neuropathy.